Magnetic Monopoles in Multivector Boson Theories - Koichiro Kobayashi; Nahomi Kan; Kiyoshi Shiraishi (Advances in High Energy Physics)
A classical solution for a magnetic monopole is found in a specific multivector boson theory. We consider the model whose [SU(2)]N+1 gauge group is broken by sigma model fields (à la dimensional deconstruction) and further spontaneously broken by an adjoint scalar (à la triplet Higgs mechanism). In this multivector boson theory, we find the solution for the monopole whose mass is MN~(4πv/g)N+1, where g is the common gauge coupling constant and v is the vacuum expectation value of the triplet Higgs field, by using a variational method with the simplest set of test functions.